2007
DOI: 10.1039/b703790b
|View full text |Cite
|
Sign up to set email alerts
|

An unpaired electron-based hole-transporting molecule: Triarylamine-combined nitroxide radicals

Abstract: A durable nitroxide radical combined with a triarylamine moiety exhibited a hole-drift mobility of 6 x 10(-3) cm(2) V(-1) s(-1), to which the aminophenyl nitroxide structure contributed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…According to Creutz and Taube, the most common MV compounds are represented by the general formula [M a n −BL−M b n +1 ], in which BL refers to an organic bridge and M a and M b are usually redox‐active inorganic or organometallic centers . Transition‐metal complexes that are decorated with additional redox‐active units represent one type of promising photoelectric materials that display intriguing electrochemical and photophysical properties and are potentially useful for applications in molecular electronics, information storage, charge transportation, light scavenging, and solar cells . In most cases, the BL backbones in these MV systems are readily oxidizable organic bridge cores, such as unsaturated sp/sp 2 ‐carbon‐based chains (oligoyne, oligoene) or fused aromatic rings (heterocycles, oligoacene) .…”
Section: Introductionmentioning
confidence: 99%
“…According to Creutz and Taube, the most common MV compounds are represented by the general formula [M a n −BL−M b n +1 ], in which BL refers to an organic bridge and M a and M b are usually redox‐active inorganic or organometallic centers . Transition‐metal complexes that are decorated with additional redox‐active units represent one type of promising photoelectric materials that display intriguing electrochemical and photophysical properties and are potentially useful for applications in molecular electronics, information storage, charge transportation, light scavenging, and solar cells . In most cases, the BL backbones in these MV systems are readily oxidizable organic bridge cores, such as unsaturated sp/sp 2 ‐carbon‐based chains (oligoyne, oligoene) or fused aromatic rings (heterocycles, oligoacene) .…”
Section: Introductionmentioning
confidence: 99%
“…[9] Since this pioneering work, the Nakahara group has reported the synthesis of a polymeric TEMPO radical derivative, poly(2,2,6,6-tetramethylpiperidinyloxy methacrylate) (PTMA), for an organic radical battery. [10] The research group of Nishide extended this work toward applications, such as radical batteries as cathode active materials, [11] organic light-emitting diodes as holeinjection layers, [12] and memory as p-type redox active materials.…”
mentioning
confidence: 99%
“…Our recent examples include triarylamine-based high-spin oligo-and poly(cationic radical)s, [36][37][38][39][40][41] polymer gels of p-phenylenediamine-based cationic radicals, 42 as well as their applications to organic devices. 43,44 During the course of this series of studies, we have shown an RT ground state multiplet polyradical using a poly[1,2,(4)-phenylenevinyleneanisylaminium] hyperbranched structure, prepared by a tedious multistep synthesis of the AB2-type monomer, followed by self-polycondensation and terminal protection. 45 This triarylamine-based cationic polyradical displayed a remarkable thermal stability even at 70 1C.…”
Section: Introductionmentioning
confidence: 99%